Ultraviolet stress luminescent material and preparation method thereof

UV stress luminescent materials produced by mixing ultraviolet luminescent powder and organic elastomer produce ultraviolet light under mechanical stimulation, solving the problem of large and electricity-demanding ultraviolet sterilization equipment in the prior art, achieving convenient and practical sterilization Effect.

CN119490750APending Publication Date: 2025-02-21KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411509547.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

In the prior art, ultraviolet sterilization requires special equipment and power supply, which is not convenient for daily use, and the equipment is large in size, which limits the convenience and practicality of sterilization.

Method used

By mixing the ultraviolet luminescent powder with organic elastomer, an ultraviolet stress luminescent material is prepared. After X-ray preirradiation, ultraviolet light is generated under mechanical stimulation to achieve a bactericidal effect.

Benefits of technology

This method simplifies sterilization operations, making sterilization more convenient and practical, and is not limited by power supply and equipment volume, and can effectively kill bacteria in daily life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490750A_ABST
    Figure CN119490750A_ABST
Patent Text Reader

Abstract

The invention discloses an ultraviolet stress luminescent material and a preparation method thereof, and belongs to the technical field of stress luminescent materials. The method comprises the following steps: (1) preparing ultraviolet light-emitting powder, wherein the ultraviolet light-emitting powder comprises Cs2NaGdF6: Pr < 3 + > powder or Cs2KGdF6: Pr < 3 + > powder; and (2) uniformly mixing the ultraviolet light-emitting powder with an organic elastomer at room temperature to obtain a free-flowing mixed colloidal body, putting the mixed colloidal body into a mold, heating the mixed colloidal body, cooling along with a furnace, taking out a product from the mold after cooling, and irradiating the product with X rays to obtain the ultraviolet stress light-emitting material. The prepared ultraviolet stress luminescent material can emit ultraviolet light under the action of mechanical stimulation, the convenience of ultraviolet sterilization operation is improved, the practicability of ultraviolet sterilization is improved, and a new way is provided for daily sterilization operation of people.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of stress luminescent materials and relates to an ultraviolet stress luminescent material and a preparation method thereof. Background Art

[0002] Ultraviolet light is a type of light radiation with a wavelength between 200-400nm. Due to its short wavelength and high energy, it can destroy the DNA and RNA molecules of microorganisms, thereby achieving a sterilization effect. Compared with chemical disinfectants, ultraviolet disinfection does not produce disinfection by-products and is more environmentally friendly. Traditional ultraviolet sterilization methods usually require the use of special equipment for special sterilization. The equipment is large in size and usually requires power supply, which is not convenient for daily use. Ultraviolet stress luminescent materials have the advantages of both stress luminescent materials and ultraviolet light. Ultraviolet stress luminescent materials can emit ultraviolet light under mechanical stimulation, and ultraviolet light has the characteristics of bactericidal effect. It can significantly simplify the sterilization operation, make sterilization more convenient and quick, and achieve sterilization without being restricted by power supply, equipment volume, etc. For example, ultraviolet stress luminescent materials pre-irradiated with X-rays are made into plasticine products. When kneading the plasticine, mechanical stimulation is generated on the ultraviolet stress luminescent materials, so that the plasticine has a bactericidal effect when used to kill bacteria on the hands. For example, the ultraviolet stress luminescent material pre-irradiated by X-rays is coated on a mop. When the mop rubs against the floor, the mechanical force generates stress luminescence to sterilize the floor. Therefore, the development of ultraviolet stress luminescent materials is of great significance for expanding the application field of stress luminescent materials and improving the application effect of ultraviolet sterilization.

[0003] Therefore, it is necessary to provide a UV stress luminescent material and a preparation method thereof, so as to prepare a material that can emit ultraviolet light under mechanical stimulation, improve the convenience of ultraviolet sterilization operation, improve the practicality of ultraviolet sterilization, and provide a new way for people's daily sterilization operations. Summary of the invention

[0004] In order to overcome the problems existing in the background technology, the present invention prepares an ultraviolet stress luminescent material by mixing an ultraviolet luminescent powder with an organic elastomer. After pre-irradiation with X-rays, when the organic elastomer and the ultraviolet luminescent powder are rubbed against each other, ultraviolet stress luminescence is generated. The ultraviolet stress luminescent material can be used to make a variety of products that need to be kneaded and squeezed when used, so that the products generate ultraviolet luminescence during use, thereby achieving the purpose of sterilization, simplifying the ultraviolet sterilization operation method, making sterilization more convenient, and improving the practicality of ultraviolet sterilization.

[0005] In order to achieve the above object, the present invention is implemented by the following technical solutions:

[0006] In one aspect, the present invention provides a method for preparing an ultraviolet stress luminescent material, the preparation method comprising the following steps:

[0007] (1) preparing ultraviolet luminescent powder, wherein the ultraviolet luminescent powder comprises Cs2NaGdF6:Pr 3+ Powder or Cs2KGdF6:Pr 3+ Powder;

[0008] (2) The ultraviolet luminescent powder is uniformly mixed with an organic elastomer at room temperature to obtain a free-flowing mixed colloid, and the mixed colloid is placed in a mold. The mixed colloid is heated and then cooled in a furnace. After cooling, the product is taken out of the mold and irradiated with X-rays to obtain an ultraviolet stress luminescent material.

[0009] Preferably, in the step (2), the heating temperature of the mixed colloid is 70° C., the heating time is 2 h, and the mass ratio of the ultraviolet luminescent powder to the organic elastomer is 1:2 to 2.5.

[0010] Preferably, the organic elastomer includes one of polydimethylsiloxane (PDMS) and silicone rubber (SG).

[0011] Preferably, the Cs2KGdF6:Pr 3+ The preparation method of ultraviolet luminescent powder comprises the following steps:

[0012] S1: Weigh Cs2CO3, KHCO3, NaF, NH4F, Gd2O3, Pr6O with a purity of 99.99% 11 The raw materials are added into an acetone solution, and ground and mixed to obtain a mixed powder A1.

[0013] S2: The mixed powder A1 obtained in step S1 is placed in an air atmosphere for pre-sintering to remove residual acetone, preliminarily remove NH3, and then ground to obtain a precursor B1 powder.

[0014] S3: Pre-sintering the precursor B1 powder obtained in step S2 in an air atmosphere to completely remove NH3, and then grinding to obtain the precursor C1 powder.

[0015] S4: Sinter the precursor C1 powder obtained in step S3 in an argon atmosphere, then cool it in the furnace, and grind it to obtain Cs2KGdF6:Pr 3+ UV luminescent powder.

[0016] Preferably, in the raw materials, the molar ratio of Cs, K, Gd, F and Pr is Cs:K:Gd:F:Pr=2:1:0.985:6:0.005.

[0017] Preferably, in step S2, the sintering temperature is 150°C and the sintering time is 7 hours; in step S3, the sintering temperature is 450°C and the sintering time is 30 minutes; in step S4, the sintering temperature is 700°C and the sintering time is 10 hours.

[0018] Preferably, the Cs2NaGdF6:Pr 3+ The preparation method of ultraviolet luminescent powder comprises the following steps:

[0019] Q1: Weigh Cs2CO3, NaHCO3, NaF, NH4F, Gd2O3, Pr6O with a purity of 99.99% 11 The raw materials are added into an acetone solution, and ground and mixed to obtain a mixed powder A2;

[0020] Q2: The mixed powder A2 obtained in step Q1 is pre-sintered in an air atmosphere to remove residual acetone and preliminarily remove NH3, and then ground to obtain a precursor B2 powder;

[0021] Q3: Pre-sintering the precursor B2 powder obtained in step Q2 in an air atmosphere to completely remove NH3, and then grinding to obtain the precursor C2 powder;

[0022] Q4: The precursor C2 powder obtained in step Q3 is sintered in an argon atmosphere, then cooled in the furnace, and ground to obtain Cs2NaGdF6:Pr 3+ UV luminescent powder.

[0023] Preferably, in the raw materials, the molar ratio of Cs, Na, Gd, F and Pr is Cs:Na:Gd:F:Pr=2:1:0.985:6:0.005.

[0024] Preferably, in step Q2, the sintering temperature is 150° C. and the sintering time is 7 hours; in step Q3, the sintering temperature is 450° C. and the sintering time is 30 minutes; in step Q4, the sintering temperature is 700° C. and the sintering time is 10 hours.

[0025] Another aspect of the present invention provides an ultraviolet stress luminescent material, which is prepared according to the above preparation method.

[0026] Beneficial effects of the present invention:

[0027] 1. The present invention prepares an ultraviolet stress luminescent material by mixing ultraviolet luminescent powder with an organic elastomer, and uses the ultraviolet stress luminescent material of the present invention as one of the raw materials to make a product that needs to be kneaded, squeezed, etc. during use. During the kneading or squeezing process, the organic elastomer and the ultraviolet luminescent powder are rubbed to induce the release of carriers captured in the trap to generate ultraviolet stress luminescence. Sterilization operations can be performed during use without the need to use special equipment for special sterilization, and it is not restricted by environmental, site, power supply and other conditions. Therefore, the use of the ultraviolet stress luminescent material of the present invention for ultraviolet sterilization is extremely convenient and practical.

[0028] 2. The ultraviolet stress luminescent material of the present invention can emit ultraviolet light that is invisible to the naked eye, and will not affect the actual use of the product due to the luminescent sterilization process.

[0029] 3. The ultraviolet stress luminescent material of the present invention has high ultraviolet stress luminescent brightness and flexibility, and can kill bacteria.

[0030] 4. During the product manufacturing process, the ultraviolet stress luminescent material of the present invention is used in a small dosage, which can sterilize without causing damage to the skin.

[0031] 5. The preparation process of the ultraviolet stress luminescent material of the present invention is simple, the cost is low and the safety is high. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 XRD patterns of the ultraviolet stress luminescent materials prepared in Example 1 and Comparative Examples 2-7 of the present invention;

[0033] Figure 2 Thermoluminescence curves of the ultraviolet stress luminescent materials prepared in Example 1 and Comparative Example 2 of the present invention;

[0034] Figure 3 X-ray luminescence spectra of the ultraviolet stress luminescent materials prepared in Example 1 and Comparative Example 2 of the present invention;

[0035] Figure 4 It is a dotted line graph of the X-ray luminescence intensity of the ultraviolet stress luminescent materials prepared in Example 1 and Comparative Examples 2-7 of the present invention;

[0036] Figure 5 This is the ultraviolet long afterglow luminescence attenuation curve of the ultraviolet stress luminescent material prepared in Example 1 of the present invention;

[0037] Figure 6 The ultraviolet stress luminescence spectrum generated by the ultraviolet stress luminescence material prepared in Example 1 of the present invention is compared with the spectrum under X-rays and the photoluminescence spectrum;

[0038] Figure 7This is a graph showing the stress luminescence test results of the material prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0039] The present invention is further described in detail below in conjunction with specific embodiments.

[0040] In the examples and comparative examples of the present invention, chemical reagents not specified were commercially available analytically pure reagents for the experiments.

[0041] Example 1

[0042] In this embodiment, the ultraviolet stress luminescent material is prepared by the following method:

[0043] (1) Weigh Cs2CO3, NaHCO3, NaF, Gd2O3, NH4F, Pr6O according to the molar ratio of Cs, Na, Gd, F, and Pr: Cs:Na:Gd:F:Pr=2:1:0.995:6:0.005 11 The raw materials are added into an acetone solution, and ground and mixed to obtain a mixed powder A1.

[0044] (2) The mixed powder is placed in an air atmosphere at 150° C. for low-temperature pre-sintering for 7 hours. During the sintering process, residual acetone and NH 3 are removed. After sintering, the precursor powder B1 is obtained by grinding.

[0045] (3) The precursor powder B1 was sintered in an air atmosphere at 450° C. for 30 minutes to completely remove NH 3 , and then ground to obtain the precursor powder C1 .

[0046] (4) The precursor powder C1 was placed in an argon atmosphere, sintered at 700°C for 10 hours, and then cooled in the furnace. Cs2NaGdF6:Pr 3+ UV luminescent powder.

[0047] (5) Step Cs2NaGdF6:Pr 3+ The powder and PDMS colloid are mixed evenly in a mass ratio of 1:2 to obtain a mixed colloidal liquid, and then the mixed colloidal liquid is placed in a pre-prepared mold, heated in an oven at 70°C for 2 hours, and then the product is cooled with the oven. After cooling, the product is taken out of the mold and irradiated with X-rays to obtain an ultraviolet stress luminescent material. The chemical formula of the ultraviolet stress luminescent material prepared in this embodiment is Cs2NaGdF6:0.005Pr 3+ And the ultraviolet stress luminescent material is in the form of a thin film.

[0048] The ultraviolet stress luminescent material prepared in this embodiment was subjected to relevant tests, wherein the XRD spectrum of this embodiment is as follows: Figure 1 The thermoluminescence curve is shown in Figure 2As shown, the X-ray luminescence spectrum is as follows Figure 3 As shown, the X-ray luminescence intensity dotted line diagram is as follows Figure 4 As shown in the figure, the ultraviolet long afterglow luminescence decay curve is as follows Figure 5 As shown, the comparison of different luminous forms is as follows Figure 6 shown.

[0049] Example 2

[0050] This embodiment adopts the same method as that of embodiment 1 to prepare the ultraviolet stress luminescent material, except that: in this embodiment, Cs2NaGdF6:Pr 3+ The powder and PDMS colloid were mixed evenly in a mass ratio of 1:2.3.

[0051] The ultraviolet stress luminescent material prepared in this embodiment has similar properties to those in embodiment 1.

[0052] Example 3

[0053] This embodiment adopts the same method as that of embodiment 1 to prepare the ultraviolet stress luminescent material, except that: in this embodiment, Cs2NaGdF6:Pr 3+ The powder and PDMS colloid were mixed evenly in a mass ratio of 1:2.5.

[0054] The ultraviolet stress luminescent material prepared in this embodiment has similar properties to those in embodiment 1.

[0055] Example 4

[0056] This embodiment adopts the same method as that of embodiment 1 to prepare the ultraviolet stress luminescent material, except that the ultraviolet luminescent powder is Cs2KGdF6:Pr 3+ .

[0057] The ultraviolet stress luminescent material prepared in this embodiment has similar properties to those in embodiment 1.

[0058] Cs2KGdF6:Pr 3+ Powder and Cs2NaGdF6:Pr 3+ The powders have similar properties in terms of chemical structure, luminescence principle, etc. Therefore, after the two powders are prepared into the final ultraviolet stress luminescent materials, they have similar properties.

[0059] Comparative Example 1

[0060] This comparative example adopts the same method as Example 1 to prepare the ultraviolet stress luminescent material, except that: in this comparative example, Cs2NaGdF6:Pr 3+ The powder is mixed with a harder epoxy resin, which is not an organic elastomer.

[0061] The stress luminescence test was carried out on the comparative material, and the results are as follows: Figure 7 shown.

[0062] pass Figure 7 It can be seen that the material prepared in this comparative example does not have stress luminescence characteristics and cannot produce ultraviolet stress luminescence, which means that the ultraviolet luminescent powder of the present invention must be mixed with the organic elastomer of the present invention to prepare the ultraviolet stress luminescent material to have ultraviolet stress luminescence characteristics.

[0063] Comparative Example 2

[0064] This comparative example adopts the same method as Example 1 to prepare the ultraviolet stress luminescent material, except that: in this comparative example, Pr is not added.

[0065] The material prepared in this comparative example was subjected to relevant tests, wherein the XRD pattern of this comparative example is as follows Figure 1 The thermoluminescence curve is shown in Figure 2 As shown, the X-ray luminescence spectrum is as follows Figure 3 As shown, the X-ray luminescence intensity dotted line diagram is as follows Figure 4 shown.

[0066] Comparative Example 3

[0067] This comparative example adopts the same method as Example 1 to prepare the ultraviolet stress luminescent material, except that: in this comparative example, the molar ratio of Cs, Na, Gd, F, and Pr is Cs:Na:Gd:F:Pr=2:1:0.99:6:0.01.

[0068] The material prepared in this comparative example was subjected to relevant tests, wherein the XRD pattern of this comparative example is as follows Figure 1 As shown, the X-ray luminescence intensity dotted line diagram is as follows Figure 4 shown.

[0069] Comparative Example 4

[0070] This comparative example adopts the same method as Example 1 to prepare the ultraviolet stress luminescent material, except that: in this comparative example, the molar ratio of Cs, Na, Gd, F, and Pr is Cs:Na:Gd:F:Pr=2:1:0.985:6:0.015.

[0071] The material prepared in this comparative example was subjected to relevant tests, wherein the XRD pattern of this comparative example is as follows Figure 1 As shown, the X-ray luminescence intensity dotted line diagram is as follows Figure 4 shown.

[0072] Comparative Example 5

[0073] This comparative example adopts the same method as Example 1 to prepare the ultraviolet stress luminescent material, except that: in this comparative example, the molar ratio of Cs, Na, Gd, F, and Pr is Cs:Na:Gd:F:Pr=2:1:0.98:6:0.02.

[0074] The materials prepared in this comparative example were subjected to relevant tests, wherein the XRD pattern of this comparative example is as follows Figure 1 As shown, the X-ray luminescence intensity dotted line diagram is as follows Figure 4 shown.

[0075] Comparative Example 6

[0076] This comparative example adopts the same method as Example 1 to prepare the ultraviolet stress luminescent material, except that: in this comparative example, the molar ratio of Cs, Na, Gd, F, and Pr is Cs:Na:Gd:F:Pr=2:1:0.975:6:0.025.

[0077] The materials prepared in this comparative example were subjected to relevant tests, wherein the XRD pattern of this comparative example is as follows Figure 1 As shown, the X-ray luminescence intensity dotted line diagram is as follows Figure 4 shown.

[0078] Comparative Example 7

[0079] This comparative example adopts the same method as Example 1 to prepare the ultraviolet stress luminescent material, except that: in this comparative example, the molar ratio of Cs, Na, Gd, F, and Pr is Cs:Na:Gd:F:Pr=2:1:0.97:6:0.03.

[0080] The materials prepared in this comparative example were subjected to relevant tests, wherein the XRD pattern of this comparative example is as follows Figure 1 As shown, the X-ray luminescence intensity dotted line diagram is as follows Figure 4 shown.

[0081] pass Figure 1 It can be seen that the ultraviolet stress luminescent materials prepared in Example 1 and Comparative Examples 2-7 of the present invention are all single-phase.

[0082] pass Figure 2 It can be seen that compared with Comparative Example 2, Example 1 has a higher UV stress luminescence intensity. 3+ The introduction of ions greatly enhances the defects inside the material, which helps to increase the intensity of ultraviolet stress luminescence in the material.

[0083] pass Figure 3 It can be seen that the ultraviolet stress luminescent material prepared by the present invention presents Gd 3+ The characteristic ultraviolet emission of ions, Pr 3+The introduction of ions can play a sensitizing role and enhance the energy transfer of Gd 3+ UV photoluminescence properties of ions.

[0084] pass Figure 4 It can be seen that the ultraviolet emission intensity of the ultraviolet stress luminescent material of the present invention increases with the increase of Pr 3+ The increase of ion concentration shows a trend of first strengthening and then weakening, which indicates that in the ultraviolet stress luminescent material of the present invention, Pr 3+ ions to Gd 3+ There is only one optimal concentration of ions for energy transfer.

[0085] pass Figure 5 It can be seen that the ultraviolet long afterglow luminescence decay of the ultraviolet stress luminescent material of the present invention gradually weakens with the extension of time, which confirms that in the present invention, the organic elastomer and the ultraviolet luminescent powder are rubbed to induce the carriers captured in the trap to be gradually released.

[0086] pass Figure 6 It can be seen that the stress luminescence, photoluminescence and X-ray irradiation spectra of the ultraviolet stress luminescent material of the present invention show the same ultraviolet emission, which confirms that the ultraviolet emission intensity of the ultraviolet stress luminescent material of the present invention is not affected by stress luminescence. The ultraviolet stress luminescent material of the present invention has good application prospects in ultraviolet sterilization.

Claims

1. A method for preparing an ultraviolet stress luminescent material, characterized in that: The preparation method comprises the following steps: (1) preparing ultraviolet luminescent powder, wherein the ultraviolet luminescent powder comprises Cs2NaGdF6:Pr 3+ Powder or Cs2KGdF6:Pr 3+ Powder; (2) The ultraviolet luminescent powder is uniformly mixed with an organic elastomer at room temperature to obtain a free-flowing mixed colloid, and the mixed colloid is placed in a mold. The mixed colloid is heated and then cooled in a furnace. After cooling, the product is taken out of the mold and irradiated with X-rays to obtain an ultraviolet stress luminescent material.

2. The method for preparing a UV stress luminescent material according to claim 1, characterized in that: In the step (2), the heating temperature of the mixed colloid is 70° C., the heating time is 2 hours, and the mass ratio of the ultraviolet luminescent powder to the organic elastomer is 1:2 to 2.

5.

3. The method for preparing a UV stress luminescent material according to claim 1, characterized in that: The organic elastomer includes polydimethylsiloxane and one of organic silicone.

4. The method for preparing a UV stress luminescent material according to claim 1, characterized in that: The Cs2KGdF6:Pr 3+ The preparation method of ultraviolet luminescent powder comprises the following steps: S1: Weigh Cs2CO3, KHCO3, NaF, NH4F, Gd2O3, Pr6O with a purity of 99.99% 11 The raw materials are added into an acetone solution, and ground and mixed to obtain a mixed powder A1; S2: pre-sintering the mixed powder A1 obtained in step S1 in an air atmosphere to remove residual acetone and preliminarily remove NH3, and then grinding to obtain a precursor B1 powder; S3: Pre-sintering the precursor B1 powder obtained in step S2 in an air atmosphere to completely remove NH3, and then grinding to obtain the precursor C1 powder; S4: Sinter the precursor C1 powder obtained in step S3 in an argon atmosphere, then cool it in the furnace, and grind it to obtain Cs2KGdF6:Pr 3+ UV luminescent powder.

5. The method for preparing a UV stress luminescent material according to claim 4, characterized in that: In the raw materials, the molar ratio of Cs, K, Gd, F and Pr is Cs:K:Gd:F:Pr=2:1:0.985:6:0.

005.

6. The method for preparing a UV stress luminescent material according to claim 4, characterized in that: In step S2, the sintering temperature is 150° C. and the sintering time is 7 hours; In the step S3, the sintering temperature is 450° C. and the sintering time is 30 minutes; in the step S4, the sintering temperature is 700° C. and the sintering time is 10 hours.

7. The method for preparing a UV stress luminescent material according to claim 1, characterized in that: The Cs2NaGdF6:Pr 3+ The preparation method of ultraviolet luminescent powder comprises the following steps: Q1: Weigh Cs2CO3, NaHCO3, NaF, NH4F, Gd2O3, Pr6O with a purity of 99.99% 11 The raw materials are added into an acetone solution, and ground and mixed to obtain a mixed powder A2; Q2: The mixed powder A2 obtained in step Q1 is pre-sintered in an air atmosphere to remove residual acetone and preliminarily remove NH3, and then ground to obtain a precursor B2 powder; Q3: Pre-sintering the precursor B2 powder obtained in step Q2 in an air atmosphere to completely remove NH3, and then grinding to obtain the precursor C2 powder; Q4: The precursor C2 powder obtained in step Q3 is sintered in an argon atmosphere, then cooled in the furnace, and ground to obtain Cs2NaGdF6:Pr 3+ UV luminescent powder.

8. The method for preparing a UV stress luminescent material according to claim 7, characterized in that: In the raw materials, the molar ratio of Cs, Na, Gd, F and Pr is Cs:Na:Gd:F:Pr=2:1:0.985:6:0.

005.

9. The method for preparing a UV stress luminescent material according to claim 7, characterized in that: In the step Q2, the sintering temperature is 150° C. and the sintering time is 7 hours; in the step Q3, the sintering temperature is 450° C. and the sintering time is 30 minutes; in the step Q4, the sintering temperature is 700° C. and the sintering time is 10 hours.

10. An ultraviolet stress luminescent material, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 9.